2006
DOI: 10.1007/s00464-004-2272-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hiatal hernia repair

Abstract: Although challenging, LRPH is a successful procedure. The high recurrence rate reported in the literature can be reduced by additional mesh reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…(3, 5, 15, 1721, 23, 24) Odds of hiatal hernia recurrence were 49% less after mesh cruroplasty, relative to the baseline group of suture cruroplasty (Figure 2. OR 0.51, 95% CI 0.30–0.87; p=0.014).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…(3, 5, 15, 1721, 23, 24) Odds of hiatal hernia recurrence were 49% less after mesh cruroplasty, relative to the baseline group of suture cruroplasty (Figure 2. OR 0.51, 95% CI 0.30–0.87; p=0.014).…”
Section: Resultsmentioning
confidence: 97%
“…(5, 15, 17, 19, 2123) Two studies reported that significantly more patients who received mesh complained of dysphagia in early follow-up compared to patients with suture repair. (16, 23) Stable dysphagia in the overall group was reported by Braghetto.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although studies have demonstrated a decrease in the PEH recurrence rate with mesh reinforcement [17,18], this technique remains controversial [15,19,20]. The use of synthetic mesh can lead to dysphagia or odyngophagia in up to 21.7% of patients, likely due to esophageal stenosis and periesophageal mesh-induced fibrosis [5,12,21,22]. In addition, Gouvas et al reported significantly more cardiac and respiratory symptoms and a delayed esophageal transit time when comparing prosthetic reinforcement to simple crural repair [23].…”
Section: Discussionmentioning
confidence: 99%